Desenvolvimento de uma vacina de RNA para leishmaniose e comparação com uma vacina baseada em antígeno recombinante - Isabela Vieira da Costa (2023)
Leishmaniases are classified as neglected tropical diseases and constitute a public health issue in various regions of the world with approximately 700,000 new cases each year. Although vaccination holds promise as an effective strategy against these diseases, there is currently no available vaccine for humans. During the Covid-19 Pandemic the RNA vaccines have emerged as lead candidates due to their speed of development and high degree of efficacy. In a previous work of our research group, the recombinant protein vaccine based on a novel leishmania antigen identified in an immunoproteomic study, designated as DTL8, yielded partial protection in BALB/c mice challenged with L. infantum. With the aim of enhancing the protective response induced by this antigen, we decided to evaluate its efficacy using an alternative vaccine platform. In this study, an RNA vaccine expressing the DTL8 antigen was developed. To achieve this, the mRNA DTL8 was encapsulated in lipid nanoparticles (LNPs) developed by CTVacinas. Comparing immunization with mRNA DTL8 encapsulated in the LNPs developed by CTVacinas to immunization with RNA encapsulated in LNPs similar to those used in the Moderna COVID-19 vaccine, we observed no significant difference in the humoral and cellular responses induced by both formulations. To evaluate the immune response and protection induced by the RNA vaccine and compare it to the immune response and protection induced by the recombinant protein (rDTL8), BALB/c mice were immunized with three doses of rDLT8 protein and Poly (ICLC) as an adjuvant, and then challenged with L. infantum. It was observed a higher production of total IgG antibodies in animals immunized with the recombinant protein as compared to those immunized with mRNA DTL8. Furthermore, after challenge with L. infantum, there was a partial reduction in parasitic load only in the spleens of animals immunized with the recombinant DTL8 protein. To evaluate the immune response and protection induced by the RNA vaccine and compare it to the immune response and protection induced by the recombinant protein vaccine against tegumentary leishmaniasis, C57BL/6 mice were immunized with three doses of the vaccines and challenged with L. amazonensis expressing luciferase. It was found that there was a similar production of total IgG antibodies in animals immunized with both the recombinant protein and mRNA DTL8. Moreover, following challenge with L. amazonensis, a partial reduction in parasitic load in the mice footpad was observed, with similar results for mice immunized with mRNA DTL8 and those receiving the recombinant DTL8 protein. Based on these results, we can conclude that immunization with mRNA DTL8 induces a protective response equivalent to that of immunization with recombinant DTL8 protein when tested in a model of tegumentary leishmaniasis.